Molecular Characterization of Hemagglutinin-Neuraminidase Protein Virus Newcastle disease (ND) in Surabaya during 2003 and 2016 - Wulandari, Innah; Rahmahani, Jola; Rahmawati, Indah; Putih, Nurvita; Azahro, Aisyah; Kusnoto, Kusnoto; Ernawati, Rahayu; Rantam, Fedik Abdul (Jurnal Medik Veteriner, 2021)
This study aimed to determine the mutation of amino acid, nucleotide homology, phylogenetic tree, epitope prediction of Hemagglutinin-Neuraminidase protein Newcastle Disease (ND) Virus isolated from traditional market around Surabaya. Samples were from 37 chicken with cloacal swab and one positive samples for control (LaSota). Samples were inoculated on embyonate chicken eggs and identified with HA test confirmed with HI test. Positive samples processed by PCR using forward and reverse primer with 503 bp RNA target. The PCR result then analyzed with sequencing. Result of sequencing analysis showed that theres similiarity between samples amino acid and vaccine isolate its effect the percentage of nucleotide homology and phylogenetic relation between isolate. Epitope NGAANNSGWGAPIHDPDYIGG have high immunogenic value at all of isolate which good as vaccine candidate.